The Study of Graphene Oxide on the Regulations and Controls of the Sol-Gel Film Structure and Its Performance - Yan Gao; Yadong Fan; Junxi Zhang; Xuanxuan Liu; Ning Wang; Shengjie Yang (Metals, 2021)
A facile strategy to boost anticorrosion potency of graphene oxide/silica hybrid sol-gel coating is developed through fully exploiting the capabilities of graphene oxide (GO). Together with a barrier to corrosives and crack inhibitor, GO was further explored herein as a regulator to regulate the gelation process and provide robust coating films with stratified microstructures and ultimately extended diffusion paths. The sol-gel coating with stratified microstructure achieved on AA5052 aluminum alloy surface afforded greatly enhanced corrosion protection capability as assessed by electrochemical measurements and immersion tests. The corrosion current density of the sample of a hybrid GO sol-gel film was about 30 times less than that of sample of pure sol-gel film sample. The regulation mechanism of GO during the film formation process and the anticorrosive protection properties of the film were discussed.